2010
DOI: 10.1186/1471-2466-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between peripheral airway function and patient-reported outcomes in COPD: a cross-sectional study

Abstract: BackgroundHealth status, dyspnea and psychological status are important clinical outcomes in chronic obstructive pulmonary disease (COPD). However, forced expiratory volume in one second (FEV1) measured by spirometry, the standard measurement of airflow limitation, has only a weak relationship with these outcomes in COPD. Recently, in addition to spirometry, impulse oscillometry (IOS) measuring lung resistance (R) and reactance (X) is increasingly being used to assess pulmonary functional impairment.MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 46 publications
6
56
0
1
Order By: Relevance
“…Although the symptoms score was strongly related to FEV1 % pred, RV/TLC % pred and LCI, LCI was the sole predictor of SGRQ total score in multivariate analysis. This suggests that respiratory quality of life following HSCT may be affected by peripheral airway dysfunction as measured by ventilation heterogeneity in a global sense and is in keeping with similar findings with FOT [43]. The absence of correlation between Sacin and both SGRQ total score and the symptoms score in this longitudinal cohort with five out of the 22 patients with clinical BO, suggests that abnormalities in the more peripheral diffusion-dependent airway compartment are too peripheral to impact on respiratory symptoms.…”
Section: Discussionsupporting
confidence: 81%
“…Although the symptoms score was strongly related to FEV1 % pred, RV/TLC % pred and LCI, LCI was the sole predictor of SGRQ total score in multivariate analysis. This suggests that respiratory quality of life following HSCT may be affected by peripheral airway dysfunction as measured by ventilation heterogeneity in a global sense and is in keeping with similar findings with FOT [43]. The absence of correlation between Sacin and both SGRQ total score and the symptoms score in this longitudinal cohort with five out of the 22 patients with clinical BO, suggests that abnormalities in the more peripheral diffusion-dependent airway compartment are too peripheral to impact on respiratory symptoms.…”
Section: Discussionsupporting
confidence: 81%
“…Two studies from Japan note that X RS relates more closely with quality of life measures than FEV 1 in both patients with asthma 60 and COPD. 61 One of the benefits of the FOT is that one can separately measure inspiratory from expiratory parameters. Using this technique, Paredi and colleagues have shown that while whole breath impulse oscillometry could not differentiate patients with asthma and COPD, patients with COPD had higher mean expiratory X5 than those with asthma, which they thought might be due to enhanced dynamic airway narrowing on expiration in these patients.…”
Section: Measurement Of Airway Resistance By the Forced Oscillation Tmentioning
confidence: 99%
“…Although in COPD patients a significant correlation between SAD and quality of life (measured by St. George's Respiratory Questionnaire, SGRQ) and dyspnoea perception (measured by mMRC scale) [8] may occur, the exact role of SAD in the clinical presentation of COPD is not yet completely understood [9]. Moreover, it is not known whether SAD may have a relationship with the impact of disease.…”
Section: Introductionmentioning
confidence: 99%